FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MELAKSANAKAN ANTENATAL CARE (ANC) DI WILAYAH KERJA PUSKESMAS WAIHAONG AMBON 2018 - Dian Setyaningrum; Josepina Mainase; Nathalie E Kailola (PAMERI, 2019)
This study aims to know what factors that related to compliance with implementing the ANC in Puskesmas Waihaong Ambon 2018. This research is an analytic cross sectional with sample of 80 respondents use a technique stratified random sampling with the approach consecutive sampling. The analysis used is Chi-Square test, with the variables studied are age, parity, education, knowledge, attitudes, support of her husband, family economy and distance of antenatal service. The results showed the percentage of respondents who dutifully implement the ANC amounted to 66.25%. There was correlation between age (p=0.04), education (p=0.001), knowledge (p<0.001), attitude (p <0.001), the husband support (p<0.001) and family economy (p=0.006) with compliance implement ANC, whereas there was no correlation between the parity (p=0.193) and the distance of antenatal service (p=0.456) with compliance to implement the ANC.